2019
DOI: 10.1097/bpo.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of General and Musculoskeletal Health Literacy Disparities in Pediatric Sports Injury Patient and Guardian Populations

Abstract: Background: Increased participation of adolescents in organized sports has led to an increase in pediatric sports injury. Limited health literacy puts patients at risk for worse outcomes through decreased compliance. We aim to evaluate the extent of health literacy disparities in pediatric sports medicine populations. Methods: Patients aged 10 to 17 years and their consenting guardians visiting clinic for treatment of a sports-related injury completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This can be achieved with the use of field testing and calculating PEM readability using easily accessible software, such as the one used in this study. Finally, measures such as providing multilingual PEMs that address cultural and linguistic barriers, which can significantly affect the health literacy of sports medicine patients, 60 may also enhance patient health literacy. Of the 5 websites assessed in this study, only the AAOS website provided multilingual content.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved with the use of field testing and calculating PEM readability using easily accessible software, such as the one used in this study. Finally, measures such as providing multilingual PEMs that address cultural and linguistic barriers, which can significantly affect the health literacy of sports medicine patients, 60 may also enhance patient health literacy. Of the 5 websites assessed in this study, only the AAOS website provided multilingual content.…”
Section: Discussionmentioning
confidence: 99%
“…Su et al reported significant disparities in musculoskeletal health literacy in pediatric sports medicine patients and caregivers [33] . They reported Caucasian guardians with private insurance as well as Englishspeaking and highly educated guardians were associated with higher directly assessed musculoskeletal health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…One root of inequitable orthopaedic care lies in disparate levels of patient comprehension of orthopaedic terminology and care instructions, which are lower in families with lower education levels, incomes, and levels of English proficiency. 26,27 This disparity is exacerbated by the inaccessibility of the patient education resources available on major society websites, many of which are written in complex language that lies above the average patient's level of reading comprehension. 28,29…”
Section: Parental Health Literacymentioning
confidence: 99%
“…30,31 Utilizing non-certified interpreters contributes to LEP patients/families facing decreased access to telehealth appointments, lower comprehension of orthopaedic terminology and treatments, and lower interpersonal satisfaction with the care that they receive. 26,27,32,33 The adult literature further demonstrates resultant disparities in quality of care and postoperative outcomes among non-English speaking patients. 6…”
Section: Languagementioning
confidence: 99%